PENINGKATAN KEMAMPUAN DAN PENDAPATAN PENGUSAHA KERUPUK IKAN HARUAN DI KELURAHAN KUIN UTARA KECAMATAN BANJARMASIN UTARA - Prihatini Ade Mayvita; Firda Herlina; Dwi Retnosari (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2017)
South Kalimantan has great potential in the development of fisheries and marine sector in order to increase regional development and community welfare. Haruan (Cork) is one of the popular local fishes in South Kalimantan. Efforts to develop the processed fish Haruan (Gabus) itself, especially in South Kalimantan is still not optimal, the processed fish that Cork is mostly done is processing of salted fish Cork and crackers. In the city of Banjarmasin itself the most processed development of Gabus fish is the processing of crackers. Haruan fish cracker processing business has not been run optimally. Processing crackers in Banjarmasin there are many in the district of North Banjarmasin, especially in the village of North Kuin. The method used in this activity is through counseling / delivery of materials, discussion, implementation, evaluation, and mentoring. The objective of this activity is expected to increase income for Haruan fish cracker processing business through innovation and technology transfer with packaging improvement, production increase and establishment of cooperatives which will ultimately improve the prosperity for the community so that the economy and tourism sector of the region can be more developed. The result of this activity is the change of Haruan Rahmatul fish cracker and Haruan Hj fish cracker. Maspah previously used simple packaging without being pressed with special tools and with less attractive labels then after the counseling and providing the aid of press machines, plastic packaging and labels, became standard packaging so it can be sold in mini market and gift shop. The owner of Haruan Rahmatul and Hj. Maspah also has recorded (bookkeeping) in their business activities. In the production process of cracker cutting that was previously manual after the help of a tool to make the cracker chip crackers in the process of cutting more efficient kerupuknya. In the case of the establishment of a cooperative for Haruan fish cracker business which is incorporated in Citra 2 group is still in process because it is still not sufficient to fund the principal savings.